An analysis of the Bango Soy Sauce Brand's Reputation and Performance - Saksono, Alvino Saka; Yuliana, Lingga (SEAN Institute, 2024)
The focus of this study is to explore how brand reputation affects brand performance using the Bango soy sauce brand as a case study. Methods of quantitative description are implemented in this study. The present study applied purposive sampling, whereby participants were selected based on their comprehension of and experience with Bango Soy Sauce products, with a buying window of July 2023 to March 2024. In all, one hundred respondents took part in this study. Version 3.3.9 of the Smart PLS analysis program is used to process partial least squares, which have been used in data analysis in research. Respondents were provided with a Google Form questionnaire with a scale from 1 to 4 that included the options for strongly disagree, disagree, agree, and highly agree. Despite the notable exception of the first section, every section of the study questionnaire is a closed statement form. It is clear from the research findings and the discussion above that brand performance is influenced by reputation. The performance of a company's brand is positively correlated with its reputation. The research's management consequence is that Indonesian society typically bases its purchasing decisions on the law of demand. When a product is priced highly, buyers are more likely to purchase it from a different brand. In order for its enthusiasts to continue enjoying Bango Soy Sauce, the brand must therefore pay attention to the stability of selling prices.